Neowaskularyzacja w tkankach oka: mechanizmy i rola czynników proi antyangiogennych - Nowak, Jerzy; Wiktorowska-Owczarek, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
Blood vessel growth and stability are under precise control of an array of pro- and anti-angiogenic factors. Under physiological conditions, actions of particular regulatory factors, as well as their mutual interactions are harmonized and balanced. Disruption of the balance between these pro- and anti-angiogenic factors is characteristic of many vascular diseases, including those occurring within the eye. Functional dominancy of proangiogenic factors (e. g., vascular endothelial growth factor, VEGF) over antiangiogenic ones (e. g., pigment epithelium-derived growth factor, PEDF), which may occur under ischemic conditions, may initiate the process of retinal or choroidal neovascularization, representing a major threat to the eyesight. This article presents and discusses current ideas concerning molecular and cellular processes underlying aberrant growth on new blood vessels in ocular tissues, in relation to microvascular ocular complications associated mainly (but not only), with diabetes mellitus, age-related macular degeneration (AMD), and retinopathy of prematurity (ROP). This review also surveys latest achievements in the field of clinically more effective future therapeutic strategies, including gene therapy applicable to the neovascular eye diseases.